Downtime cost analysis of offloading operations under irregular waves in Malaysian waters - Patel, M.S. (Techno Press, 2020)
The objective of this study was to evaluate the downtime cost of side-by-side offloading operations in Malaysian waters. With the help of a numerical time domain tool, the structure and cable response of moored FPSO vessel was simulated for heading and beam sea-states under irregular waves. The weather downtime was assessed by comparing the response under operational wave condition with the pre defined industrial safe offloading criteria. Additionally, two cases of cable failure were simulated for each sea-state. The novel study on downtime cost was presented for three different location of Malaysia subcontinent for which the location specific wave scatter diagram facilitated to estimate the probability of occurrence of operational wave condition. It was concluded that an unpredictable increment in wave height by 0.5 m can significantly impact the production cost. Â© 2020 Techno-Press, Ltd.